2012
DOI: 10.1074/jbc.m111.330803
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Chains of Syndecan-1 Regulate Ectodomain Shedding

Abstract: Background: Syndecan ectodomains shed by cells can enhance progression of cancer, inflammatory disease, and pathogen infection. Results: Reducing the amount of heparan sulfate present on syndecan core proteins increases shedding of the ectodomain. Conclusion: Heparan sulfate chains suppress syndecan shedding. Significance: Therapeutic inhibition of heparan sulfate degradation could slow disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 39 publications
8
94
1
Order By: Relevance
“…Interestingly, HS has been shown to bind and modulate the activity of several sheddases. 189,190 Contrary to our findings for syndecan-4, shedding of syndecan-1 is suppressed by the presence of HS GAG chains, 191 consistent with the acceleration of shedding of this proteoglycan by heparanase. 192 The juxtamembrane domain of syndecan-4 has been shown to be sensitive to proteolytic cleavage in vitro, 98 however we observed only a slight reduction in constitutive shedding of syndecan-4 after removal of this domain.…”
Section: Syndecan-4 Shedding In Cardiac Inflammation: Regulation Consupporting
confidence: 51%
“…Interestingly, HS has been shown to bind and modulate the activity of several sheddases. 189,190 Contrary to our findings for syndecan-4, shedding of syndecan-1 is suppressed by the presence of HS GAG chains, 191 consistent with the acceleration of shedding of this proteoglycan by heparanase. 192 The juxtamembrane domain of syndecan-4 has been shown to be sensitive to proteolytic cleavage in vitro, 98 however we observed only a slight reduction in constitutive shedding of syndecan-4 after removal of this domain.…”
Section: Syndecan-4 Shedding In Cardiac Inflammation: Regulation Consupporting
confidence: 51%
“…We previously demonstrated that syndecan-1 isolated from the CAG HPSE-high cells used in the present work is smaller in size than the syndecan-1 isolated from the HPSE-low cells, indicative of its heparan sulfate being trimmed by heparanase (23). This smaller form of syndecan-1 is also more rapidly shed from the cell surface, indicating that heparanase also influences syndecan-1 location (23,26). Moreover, when recombinant heparanase was added to glioma cells, it induced an accumulation of syndecan-1 within endosomes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Images were taken using FEI Tecnai F20 electron microscope operated at 200 kv, and images were captured on a 4k ϫ 4k CCD camera. For Western blots of exosome proteins, samples were loaded onto a 10% or a 4 -20% gradient SDS-polyacrylamide gel (Bio-Rad), transferred to a positively charged nylon membrane (Nytran SPC, Schleicher & Schuell), and probed with antibody as described (26). Antibodies used were against: heparanase (affinity-purified polyclonal antibody 1453 (27)), flotillin-1 (Abcam), clathrin heavy chain (Abcam), and CD63 (Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…The syndecan 1 ectodomain can also influence Fgf2 mitogenic activity and migration (Eriksson and Spillmann, 2012;Chen et al, 2009). Upon treating cells with heparin lyase to remove attached HS chains, the amount of the syndecan 1 ectodomain in conditioned medium is increased, suggesting that having less HS on the core protein will increase the shedding (Ramani et al, 2012). One might speculate that the specific sulfation pattern of syndecan 1 CS/DS, like the absence of 2-O sulfation, would have an impact on the sensitivity for proteolytic action, so that shedding by matrilysin (Endo et al, 2003) results in an increased ectodomain and signals back to the cells (Eriksson and Spillmann, 2012).…”
Section: Discussionmentioning
confidence: 99%